2021
DOI: 10.1073/pnas.2105014118
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the bilayer-mediated toppling mechanism of a folate-specific ECF transporter by cryo-EM

Abstract: Energy-coupling factor (ECF)–type transporters are small, asymmetric membrane protein complexes (∼115 kDa) that consist of a membrane-embedded, substrate-binding protein (S component) and a tripartite ATP-hydrolyzing module (ECF module). They import micronutrients into bacterial cells and have been proposed to use a highly unusual transport mechanism, in which the substrate is dragged across the membrane by a toppling motion of the S component. However, it remains unclear how the lipid bilayer could accommodat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 65 publications
(83 reference statements)
3
26
0
Order By: Relevance
“…These studies reveal that ECF-S remains monomeric in the absence of substrate, likely adopting an ‘outward’ facing orientation that enables substrate binding from the extracytosolic space. 22,34,35 Once substrate is bound, ECF-S undergoes a ‘toppling’ conformational change to an ‘inward’ orientation where it engages the ECF-T, ECF-A, ECF-A’ complex in a manner that facilitates substrate release into the cytosol. ATP hydrolysis in the ECF complex then causes release of apo ECF-S, which reverts to its monomeric ‘outward’ orientation ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reveal that ECF-S remains monomeric in the absence of substrate, likely adopting an ‘outward’ facing orientation that enables substrate binding from the extracytosolic space. 22,34,35 Once substrate is bound, ECF-S undergoes a ‘toppling’ conformational change to an ‘inward’ orientation where it engages the ECF-T, ECF-A, ECF-A’ complex in a manner that facilitates substrate release into the cytosol. ATP hydrolysis in the ECF complex then causes release of apo ECF-S, which reverts to its monomeric ‘outward’ orientation ( Figure 5A ).…”
Section: Discussionmentioning
confidence: 99%
“…ATP hydrolysis in the ECF complex then causes release of apo ECF-S, which reverts to its monomeric ‘outward’ orientation ( Figure 5A ). 22,35 Considering the similarity of subunits, the proposed mechanism of ECF import has implications for how EetB might function in FAD export. Simply reversing the relationship between ECF-S with the rest of the ECF transporter complex could reverse the direction of transport ( Figure 5B ).…”
Section: Discussionmentioning
confidence: 99%
“…While little is known about the mechanism of ECF export, previous research has generated considerable evidence about the basis of ECF import. These studies reveal that ECF-S remains monomeric in the absence of a substrate, likely adopting an “outward”-facing orientation that enables substrate binding from the extracytosolic space ( 23 , 35 , 36 ). Once the substrate is bound, ECF-S undergoes a “toppling” conformational change to an “inward” orientation where it engages the ECF-T–ECF-A–ECF-A′ complex in a manner that facilitates substrate release into the cytosol.…”
Section: Discussionmentioning
confidence: 92%
“…ATP hydrolysis in the ECF complex then causes the release of apo-ECF-S, which reverts to its monomeric outward orientation ( Fig. 5A ) ( 23 , 36 ). Considering the similarity of subunits, the proposed mechanism of ECF import has implications for how EetB might function in FAD export.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations and cryo-EM spectroscopy revealed that the protein-induced membrane deformations enable the toppling of the S-component across the membrane and its interaction with the ECF module. 4,5 This unique architecture and mechanism of action make the ECF transporters fascinating and challenging targets. Over the past decade, several structural and functional studies have unravelled their mechanism of transport.…”
mentioning
confidence: 99%